Revisiting Spillover Effect - Huruta, Andrian; Hananto Andreas, Hans; Louis Forestal, Roberto; Elangovan, Anboli; Francis Diaz, John (Industrija, 2021)
This study analyzes the spillover effect of markets’ commodity, exchange rate, and stock price. Starting from July 1, 2009, the daily data to December 31, 2019, are conducted in our study. The GARCH-ARMA approach has been undertaken in this study. The results show that four pairs experience the unidirectional (positive) spillover effect of return. Yet, the spillover effect of volatility shows a two-way relationship (both positive and negative) between commodity markets, stock prices, and exchange rates. To conclude, both stock prices and gold are volatility’s net transmitters to other markets, while the EURUSD market is some markets’ net receiver of volatility.